Cloud computing in information management - Ishak, Isma; Kamaruddin, Faten Elina (Universiti Teknologi MARA, Johor, 2025)
Cloud computing is a revolutionary idea that has altered how businesses handle, store, and analyse data in the ever-changing world of information technology. For university students majoring in information management, understanding cloud computing is now a necessary ability instead of an optional one. The purpose of this chapter is to present a complete image of cloud computing by talking about its key ideas, distinct models, and a critical look at its merits and cons, especially when it comes to managing information.